Radiation-Induced Cellular and Molecular Alterations in Asexual Intraerythrocytic Plasmodium falciparum - Oakley, Miranda S. (Oxford University Press, 2013)
Background. γ-irradiation is commonly used to create attenuation in Plasmodium parasites. However, there are no systematic studies on the survival, reversion of virulence, and molecular basis for γ-radiation–induced cell death in malaria parasites. Methods. The effect of γ-irradiation on the growth of asexual Plasmodium falciparum was studied in erythrocyte cultures. Cellular and ultrastructural changes within the parasite were studied by fluorescence and electron microscopy, and genome-wide transcriptional profiling was performed to identify parasite biomarkers of attenuation and cell death. Results. γ-radiation induced the death of P. falciparum in a dose-dependent manner. These parasites had defective mitosis, sparse cytoplasm, fewer ribosomes, disorganized and clumped organelles, and large vacuoles—observations consistent with “distressed” or dying parasites. A total of 185 parasite genes were transcriptionally altered in response to γ-irradiation (45.9% upregulated, 54.1% downregulated). Loss of parasite survival was correlated with the downregulation of genes encoding translation factors and with upregulation of genes associated with messenger RNA–sequestering stress granules. Genes pertaining to cell-surface interactions, host-cell remodeling, and secreted proteins were also altered. Conclusions. These studies provide a framework to assess the safety of γ-irradiation attenuation and promising targets for genetic deletion to produce whole parasite-based attenuated vaccines.